2017
DOI: 10.1002/jcp.26106
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐based release analysis of the JC virus agnoprotein regions: A role for the hydrophilic surface of the major alpha helix domain in release

Abstract: Agnoprotein (Agno) is an important regulatory protein of JC virus (JCV), BK virus (BKV) and simian virus 40 (SV40) and these viruses are unable to replicate efficiently in the absence of this protein. Recent 3D-NMR structural data revealed that Agno contains two alpha-helices (a minor and a major) while the rest of the protein adopts an unstructured conformation (Coric et al., 2017, J Cell Biochem). Previously, release of the JCV Agno from the Agno-positive cells was reported. Here, we have further mapped the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This high level of conservation suggests that they also play similar roles in release of BKV and SV40 agnoproteins. Note that, in addition to JCV agnoprotein, the release of BKV and SV40 agnoprotein was also observed (unpublished data; Saribas, White, et al, ). The exact mechanism of agnoprotein release is currently unknown, however, the involvement of the ER to Golgi pathway was previously suspected using a specific inhibitor of this pathway, Brefeldin A (Otlu et al, ).…”
Section: Agnoprotein Of Polyomavirusesmentioning
confidence: 75%
See 3 more Smart Citations
“…This high level of conservation suggests that they also play similar roles in release of BKV and SV40 agnoproteins. Note that, in addition to JCV agnoprotein, the release of BKV and SV40 agnoprotein was also observed (unpublished data; Saribas, White, et al, ). The exact mechanism of agnoprotein release is currently unknown, however, the involvement of the ER to Golgi pathway was previously suspected using a specific inhibitor of this pathway, Brefeldin A (Otlu et al, ).…”
Section: Agnoprotein Of Polyomavirusesmentioning
confidence: 75%
“…Agnoprotein was recently found to be released from the agnoprotein‐positive cells in relatively significant amounts (Otlu et al, ; Saribas, White, et al, ). The structure‐based release analysis studies clearly showed that the hydrophilic surface of the major α‐helix domain of the protein plays critical roles in this process (Saribas, White, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting plasmid was designated as Bluescript KS (+)-JCV Mad-1 (T524-Stop). The coding sequences of ORF1, ORF1M (Ile23Met), and ORF2 were subcloned into a pCGT7 vector (Saribas, White, & Safak, 2017) at XbaI/BamHI sites, where ORFs were tagged with a T7-tag sequence (MASMTGGQQMG) at their N-termini. The resulting expression plasmids were designated as pCGT7-JCV ORF1, pCGT7-JCV ORF1M (Ile23Met), and pCGT7-JCV ORF2.…”
Section: Plasmidsmentioning
confidence: 99%